Citrus BMP Implementation in Florida's Gulf Citrus Production Area: Nutrients - Sanjay Shukla; Robert E. Rouse; S. S. Shukla; Edward A. Hanlon; Kenneth Portier; Thomas A. Obreza (EDIS, 2011)
In 2005 we conducted a survey in cooperation with Gulf Citrus Growers Association and FDACS to quantify the current level of Best Management Practices (BMP) implementation and to identify BMPs that might be adopted if a cost-share program was available. This publication describes the survey and discusses the findings regarding nutrient BMPs. This 11-page fact sheet was written by S. Shukla, R.E. Rouse, S.S. Shukla, E.A. Hanlon, K. Portier, and T.A. Obreza, and published by the UF Department of Agricultural and Biological Engineering, August 2010.